2019
DOI: 10.1007/s13127-019-00416-0
|View full text |Cite
|
Sign up to set email alerts
|

The Caribbean enigma: the presence of unusual cryptic diversity in intertidal mites (Arachnida, Acari, Oribatida)

Abstract: The definition, as well as the existence of cryptic species, is still a subject of controversial debates. Some scientists claim that cryptic diversity is a real phenomenon that should be extensively studied while others argue that cryptic species do not exist as they are nothing more than an incompatibility of species concepts. We investigated the enigmatic case of two widely distributed Caribbean intertidal oribatid mites, Carinozetes bermudensis and Carinozetes mangrovi, consisting of five distinct genetic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…Gene bank accession numbers are given in Table S1 . In congruence with the previous work of Pfingstl et al 19 , we could confirm the existence of five genetic lineages within the genus Carinozetes . Maximum likelihood (ML), Bayesian inference, and neighbor-joining analyses produced largely congruent phylogenies for all clades.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Gene bank accession numbers are given in Table S1 . In congruence with the previous work of Pfingstl et al 19 , we could confirm the existence of five genetic lineages within the genus Carinozetes . Maximum likelihood (ML), Bayesian inference, and neighbor-joining analyses produced largely congruent phylogenies for all clades.…”
Section: Resultssupporting
confidence: 92%
“…Morphological structures are often commensurate with phylogenetic relatedness because less morphological divergence is supposed to have occurred in closely related taxa compared with those that are more distantly related 20 . The Carinozetes species used in our study are closely related and were recently shown to consist of five morphologically identical but genetically distinct lineages with differing ecologies 19 , which allows us to observe the interplay of claw morphology, ecology and phylogenetic relatedness below species level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that syntopically found specimens congruently clustered in the single gene trees derived from COI-2 and 18S sequence data (and also the D3-28S data, considering the poor resolution of this marker), additionally indicates that there is no ongoing gene flow between the respective groups. Genetic distances, based on the COI sequences, among these six main groups amounted to 12.7–19.6% (uncorrected p -distances), which is well in line with previously reported species-level divergences in other oribatid mites ( Heethoff et al, 2007 ; Pfingstl, Baumann & Lienhard, 2019 ; Schäffer et al, 2010 ; Schäffer, Kerschbaumer & Koblmüller, 2019 ) and suggests that this radiation is not of recent origin. Despite intensive investigations, it was not possible to differentiate these groups morphologically.…”
Section: Discussionsupporting
confidence: 89%
“…More thorough studies conducted after molecular genetic analyses (for example, on fine-scale morphology, behavior, chemical properties) usually support the new species status (Skoracka et al 2015 ), which indicates that ‘cryptic’ species often only are an example of inadequate taxonomy. In mites, several studies demonstrated that genetically well separated species did not show differences in distinct morphological characters and only differed slightly in morphometric analyses (e.g., Knee et al 2012 ; Pfingstl et al 2019 ; Schäffer et al 2019 ). The morphometric differences revealed in S. carinthiacus thus point to the possible existence of a species complex, even more so as phenotypic variation analyzed by GMM can be as sensitive as molecular data (Karanovic et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%